Efektivitas Metode Learning Starts With A Question Berbantuan Media Poster dalam Meningkatkan Motivasi Belajar di MAN 4 Aceh Besar - *Maulida Maulida; Zulfan Zulfan; Sufandi Iswanto (Universitas Syiah Kuala, 2021)
This title was researched because of the problem of lack of student motivation in learning history. This study aims to determine the effectiveness of students' history learning motivation in class X IPS 1 by using the learning starts with a question method assisted by poster media and to determine student responses to the application of the LSQ method assisted by poster media. The type of research used in this research is descriptive statistics with a quantitative approach. As for the subject of this research are students of class X IPS-1, totaling 23 students using data collection instruments in the form of observations, questionnaires, and tests. The results of the observation of students' learning motivation are 91.25% (Highly Motivated), the test results show that the students' classical mastery scores reach 95% (Very Good), and the results of the questionnaire calculation show that the average learning motivation is 77.89 (High). Thus, it can be concluded that the use of the LSQ method with the aid of poster media is effective in increasing students' motivation to learn history